Flow modulation metalorganic vapor phase epitaxy of GaN at temperatures below 600 ºC. (29th July 2020) - Reilly, Caroline E; Mates, Thomas E; Webb, Micah; Nakamura, Shuji; DenBaars, Steven P; Keller, Stacia
Abstract: Heterogeneous integration of materials systems for devices and circuits is becoming of increasing interest, particularly for the wide bandgap nitrides in both optoelectronic and electronic applications. However, typical high growth temperatures of GaN by metalorganic vapor phase epitaxy prevent the growth of GaN on wafers with temperature sensitive materials. This work presents a flow modulation epitaxy (FME) growth scheme which allows for step-flow growth of GaN at temperatures below 600 °C. The utilization of a pulsed growth scheme such as FME allows for the mitigation of challenges associated with limited motion of adatoms at lower growth temperatures. Factors such as temperature, precursor flow rate, cycle time, and film thickness were explored. Under optimized conditions, step-flow growth of GaN films at 550 °C was demonstrated. In addition to an improved surface morphology over layers grown in the conventional continuous growth mode, the carbon and oxygen residual impurity concentrations in the FME grown layers were significantly lower, with carbon and oxygen contents of 9 × 10 17 cm −3 and 8 × 10 16 cm −3, respectively. Although the growth rate of the low temperature growth was very slow, ∼ 0.006 Å/s, the flow modulation growth scheme developed here provides a pathway towards further integration of GaN with temperature sensitive materials.